Inovasi Layanan khusus untuk Meningkatkan Perkembangan Sosial Emosional Anak Usia Dini - Selvia Fernanda Putri; Sofi Umi Muslimah; Fetty Ernawati (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2026)
Early Childhood Education (ECE) is an important foundation in shaping the quality of human resources because early childhood is in the golden age period, which requires optimal stimulation to support all aspects of development, especially social-emotional development. Children’s social-emotional development still faces various challenges, such as limited ability to control emotions, difficulty interacting with peers, and low ability to express feelings appropriately. This study aims to analyze the implementation of special service management through collaboration with parents in improving early childhood social-emotional development. The research method used is descriptive qualitative research with a library research approach through collecting data from books, scientific journals, academic articles, and other relevant official documents. The data were analyzed using content analysis techniques to identify patterns, relationships, and main findings. The results show that special service management in Early Childhood Education includes counseling services,transportation, school health services, extracurricular activities, cooperatives, and other supporting services that cansupport children’s development. Collaboration between teachers and parents through active communication, involvement in school programs, and consistent stimulation at home has been proven to support children’s social-emotional development optimally. Therefore, synergy between Early Childhood Education institutions and parents is an important factor in the success of early childhood education services.